Catalytic Biorefining of Cigarette Butts Recycling Waste - Eric Borges Ribeiro; Maria Betânia d’Heni Teixeira; Thérèse Hofmann Gatti; Romulo Davi Albuquerque Andrade; Paulo Anselmo Ziani Suarez (Chemistry)
Urban solid waste (USW) is a promising alternative source of valuable chemical compounds. It is considered an adsorbent material due to its chemical structure, porosity and electronic charge available to form chemical bonds and can be recovered or transformed for use in bioprocesses and industrial applications. This is the case with cigarette butts (CBs), which consist of thousands of substances that can be chemically converted for various purposes. This work showed high efficiency in the production of cellulose mass from the recycling of CBs, a patented technology in operation at the company Poiato Recicla—SP. The lignin-like solid (LLS)—a material obtained from the recycling of cigarette butts (CBs) by catalytic transfer hydrogenation (CTH), under non-rigorous conditions—showed high efficiency in its conversion into molecules of great interest. In the bio-oil obtained, characterized by analyses such as GCMS and RMN 2D HSQC, a mixture of predominantly hydrocarbons (many of them with cyclic and/or branched chains) was identified in almost all the experiments. This method demonstrates the potential of the TCH process for SSLs and completes the recycling chain designed for CBs, promoting their complete conversion into chemical compounds of greater interest.